HUBUNGAN BEBAN KERJA DAN PENGETAHUAN DENGAN PELAKSANAAN KESELAMATAN PASIEN (PATIEN SAFETY): REVIEW: beban kerja dan pengetahuan pada pasien safety - Purnomo, Roni; Ningtiyas, Rahaju; Setiawan, Cristina Sunadi (Universitas Harapan Bangsa Purwokerto, 2021)
ABSTRACT Background: Patient safety is important in supporting the quality and quality of a health service provider. Workload and knowledge have an important role in reducing the risk of accidents or disability during treatment. Purpose: To find out the relationship between workload and knowledge with patient safety. Method: This research is a literature review using Google Scholar. The final journals obtained were 6 journals that had passed the screening. Results: From the analysis of 6 journals, it was found that there was a relationship between workload and knowledge with patient safety. Conclusion: There is a relationship between workload and knowledge with patient safety